Efek Satisfaction Pada Loyalty Pendengar Radio Suara Surabaya - Supriyonoi, Supriyono (Jurnal Riset Ekonomi dan Bisnis, 2008)
The radio is media having reach enough wide to segment of certain market as well as effective in forwarding of information. Besides also can function as entertainment amusement media, business media, education media as well as culture media. Now, many in order the customer satisfies. If customer satisfaction has been reached, of course will generate faithfulness or customer loyalty. This forces broadcast radio organizer to comprehend customer behavior and at the same time plans, designs, executes and controls marketing strategy that’s most precise in order that company can create and maintains customer satisfaction and customer loyalty, so can stay and can grow in the future. This research applies primary data obtained from responder answer by using purposive sampling technique. To fulfill purpose of research, hypothesis tested by using structural equation model (SEM). From result of hypothesis  examination conclude that customer satisfaction has significant influence and positive to customer loyalty of Suara Surabaya radio hearer.Keywords : Customer Satisfaction, Customer Loyalty